A university-industry cooperation model for small and medium enterprises: the case of Chengdu KEDA Optoelectronic Technology Ltd. - Peng, S.; Ferreira, F.; Zheng, H. (International Journal of Learning and Change, 2017)
In this study, we develop a firm-dominated incremental cooperation model. Following the critical review of current literature and various cooperation models, we identified a number of strengths and shortcomings that form the basis for our framework. The objective of our theoretical model is to contribute to overcome the existing gap within academic literature and theory pertaining to University-Industry (U-I) cooperation (in the context of small- and medium-sized enterprises (SMEs)) while improving practice in real world context. The uniqueness of the new cooperation model provides a number of benefits over the previous ones in relation to better communication channels and an incremental process that aids in the elimination of risk and cost. Therefore, the probabilities of success for this model, especially in the context of SMEs, should be underlined.